Azadirachtin on Oligonychus yothersi in yerba mate Ilex paraguariensis - Alves,Luis Francisco Angeli (2016)
ABSTRACT: The red mite Oligonychus yothersi is one of the main pests of yerba mate in Brazil The damage this mite causes leads to leaf drop and decreased production. There are no registered acaricides for use in yerba mate; thus, laboratory and field experiments were performed to evaluate the effect of azadirachtin (Azamax(r), 250mL 100L-1) for the control of the red mite in yerba mate. In the laboratory, azadirachtin was applied to yerba mate leaf disks before (residual contact) and after (direct contact) infestation with 15 newly emerged red mite adult females. The effect of azadirachtin on mite behavior was evaluated in arenas with treated and untreated yerba mate leaves, and the number of mites in both areas was recorded. Ovicidal action was evaluated by applying azadirachtin to eggs and recording egg hatching. In the field, two applications of the product were performed (1L spray liquid plant-1) with a 7-day interval. The numbers of living mites were evaluated at 7, 14 and 21 days following the first application on randomly collected leaves. It was observed 86.6 and 91.4% of mortality following 24h of residual and direct contact, respectively. Repellent (62% of individuals leaving the treated area) and ovicidal (98.9% decrease in egg hatching) effects were also observed. The mite population in the yerba mate crop field had decreased by 59.6% at 14 days after the first application of azadirachtin. The results show the potential of azadirachtin for the control of O. yothersi in yerba mate in Brazil.